Catalyst for synthesizing methacrylate and preparation method thereof

Through the method of combining tetrabutyl orthosilicate with phospholipids, cholesterol and zirconium nitrate support, a catalyst structure with a deposited zirconium layer coated with silica was formed, which solved the problems of low activity and poor selectivity of the existing catalysts, and achieved efficient and reusable methacrylate synthesis.

CN119701912APending Publication Date: 2025-03-28ZIBO WONDERFUL CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411876978.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing catalysts have low catalytic reaction activity, poor repeatability, and poor MMA selectivity in methacrylate synthesis.

Method used

Tetrabutyl orthosilicate is combined with phospholipids and cholesterol. Zirconium nitrate is supported outside the bilayer hydrophilic structure of the phospholipid vesicles. A special structure of deposited zirconium layer coated with silica is formed by calcination, which increases the specific surface area and structural stability of the catalyst.

Benefits of technology

The catalytic performance and reaction conversion rate of the catalyst are significantly improved, the selectivity and yield of MMA are enhanced, and the catalyst can be reused many times and maintained high activity, extending the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701912A_ABST
    Figure CN119701912A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of methacrylate synthesis, in particular to a catalyst for methacrylate synthesis and a preparation method thereof. The catalyst for synthesizing methacrylate is prepared from the following raw materials in parts by mass: 1 to 3 parts of tetrabutyl orthosilicate, 5 to 10 parts of phospholipid, 1 to 2 parts of cholesterol, 0.1 to 1 part of zirconium nitrate, 5 to 10 parts of cesium nitrate and 1 to 2 parts of graphene oxide. The obtained catalyst is used in a fixed bed reactor, methacrylate can be continuously produced with high activity and high selectivity, the catalyst is good in stability and good in continuous repeated regeneration effect, and the preparation method of the catalyst is simple, easy to control, suitable for large-scale industrial application and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methacrylate synthesis, and in particular to a catalyst for methacrylate synthesis and a preparation method thereof. Background Art

[0002] Methyl methacrylate, referred to as MMA, is an important organic chemical raw material with a wide range of uses. It is mainly used as an important intermediate and polymer monomer in organic synthesis. It is widely used in coatings, textiles, leather making, adhesives and other industries.

[0003] At present, the technology of synthesizing acrylic acid in one step by using acetic acid and formaldehyde as raw materials through aldol condensation reaction has become one of the research hotspots in this field, and the catalyst used is one of the most critical technologies in the synthesis process.

[0004] At present, there have been many patent literature reports on the research of catalysts for synthesizing methacrylate from formaldehyde and methyl propionate at home and abroad. At present, the main research is on the performance of catalysts with SiO2, ZrO2, SiO2-Al2O3, Ca(OH)2, molecular sieves, activated carbon, etc. as carriers and Cs as the main active component.

[0005] However, existing catalysts have low catalytic activity, poor reproducibility, and poor MMA selectivity. Therefore, developing an efficient catalytic reaction process is of great practical significance. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a catalyst for methacrylate synthesis and a preparation method thereof.

[0007] A catalyst for methacrylate synthesis, the raw materials of which include, by mass, 1-3 parts of tetrabutyl orthosilicate, 5-10 parts of phospholipids, 1-2 parts of cholesterol, 0.1-1 parts of zirconium nitrate, 5-10 parts of cesium nitrate and 1-2 parts of graphene oxide.

[0008] Preferably, the phospholipid is lecithin or soybean lecithin.

[0009] Preferably, the particle size of graphene oxide is 3-10 μm and the bulk density is 0.06-0.07 g / cm 3 .

[0010] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0011] S1. Add tetrabutyl orthosilicate, phospholipids and cholesterol to chloroform and mix evenly, remove chloroform by rotary evaporation, add to phosphate buffer solution, add zirconium nitrate and ultrasonically treat for 10-20 minutes, adjust the pH value of the system to 8.5-9.5, stir at room temperature for 1-2 hours, filter, vacuum dry, roast at 400-450° C. for 1-2 hours, and cool to room temperature to obtain a composite carrier;

[0012] S2. Add cesium nitrate and graphene oxide to deionized water and stir evenly, add the composite carrier, ultrasonically treat at 40-50°C for 1-2h, let stand for 5-10h, hydrothermally react at 195-210°C for 5-10h, cool to room temperature, filter, wash, and freeze-dry.

[0013] Preferably, in S1, the pH value of the phosphate buffer solution is 5.2-6.5.

[0014] Preferably, in S1, the ultrasonic frequency is 2-6 kHz.

[0015] Preferably, in S2, the ultrasonic frequency is 2-6 kHz.

[0016] The method for using the methacrylate synthesis catalyst is as follows: the methacrylate synthesis catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:5-10, and the feed space velocity is 3.5-6.5h -1 , the reaction temperature is 350-400℃.

[0017] The specific reaction equation is as follows: CH3CH2COOCH3+HCHO→CH2=C(CH3)COOCH3+H2O

[0018] Preferably, the reaction pressure is 0.1-0.2 MPa.

[0019] Beneficial effects:

[0020] The present invention adopts tetrabutyl orthosilicate to compound with phospholipid and cholesterol, and confines tetrabutyl orthosilicate in the double-layer hydrophobic structure of phospholipid vesicles, and loads zirconium nitrate outside the double-layer hydrophilic structure of phospholipid vesicles; in an alkaline environment, tetrabutyl orthosilicate is hydrolyzed in the hydrophobic layer, and zirconium nitrate forms a precipitation structure layer loaded outside the closed double-layer structure; and after calcination, a special structure of a deposited zirconium layer covering silicon dioxide is formed, which not only has a large specific surface area, effectively increases the specific surface area of ​​the catalyst, and has high catalytic activity, but also has a good loading effect on cesium nitrate and graphene oxide, and has high structural stability.

[0021] The applicant has found that the present invention can greatly improve the catalytic performance of the catalyst, improve the reaction conversion rate, and at the same time improve the selectivity and yield of the target product MMA; and can be reused multiple times while maintaining high catalytic activity and selectivity, thereby extending the service life of the catalyst.

[0022] The present invention can effectively avoid the aggregation or agglomeration of active cesium and zirconium on the surface of the carrier, ensure high dispersion, and interaction with the carrier. The active components cesium and zirconium are evenly dispersed on the carrier with a relatively large surface area, which not only exposes more active centers and has high catalytic activity, but also can slow down the deactivation of the catalytic process and effectively extend the catalytic life.

[0023] The catalyst obtained by the present invention is used in a fixed bed reactor, and can produce methacrylate continuously, with high activity and high selectivity, and the catalyst has good stability and good continuous repeated regeneration effect. The catalyst preparation method of the present invention is simple and easy to control, suitable for large-scale industrial application, and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a comparison chart of specific surface area and pore volume of the catalysts obtained in Example 5 and Comparative Examples 1-3.

[0025] Figure 2 The figure is a comparison chart of the formaldehyde conversion rate and methyl propionate conversion rate after the catalysts obtained in Example 5 and Comparative Examples 1-3 participate in the catalytic reaction.

[0026] Figure 3 This is a comparison chart of the selectivity and yield of methacrylate after the catalysts obtained in Example 5 and Comparative Examples 1-3 participated in the catalytic reaction.

[0027] Figure 4 It is a comparison chart of the cyclic catalytic performance of the catalysts obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0028] The present invention will be further explained below in conjunction with specific embodiments.

[0029] The soybean lecithin used in the following was purchased from Ningbo Xifeng Biotechnology Co., Ltd. The graphene oxide used in the following was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with a product number of HGP-10, a particle size of 10 μm, and a bulk density of 0.07 g / cm 3 .

[0030] Example 1

[0031] A catalyst for synthesizing methacrylate, the raw materials of which include: 1g of tetrabutyl orthosilicate, 5g of soybean lecithin, 1g of cholesterol, 0.1g of zirconium nitrate, 5g of cesium nitrate and 1g of graphene oxide.

[0032] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0033] S1. Tetrabutyl orthosilicate, soybean lecithin and cholesterol were added to 20 g of chloroform and mixed evenly. The chloroform was removed by rotary evaporation. The mixture was added to 10 g of phosphate buffer solution with a pH of 5.2-6.5. Zirconium nitrate was added and ultrasonically treated for 10 min at an ultrasonic frequency of 2 kHz. The pH value of the system was adjusted to 8.5-9.5 with aqueous ammonia. The mixture was stirred at room temperature for 1 h, filtered, vacuum dried, calcined at 400° C. for 1 h, and cooled to room temperature to obtain a composite carrier.

[0034] S2. Add cesium nitrate and graphene oxide to 20 g of deionized water and stir evenly, add the composite carrier, ultrasonically treat at 40°C for 1 h, the ultrasonic frequency is 2 kHz, let stand for 5 h, put into the inner tank of the hydrothermal reactor, hydrothermally react at 195°C for 5 h, cool to room temperature, filter, wash, and freeze-dry.

[0035] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:5, and the feed space velocity is 3.5h -1 , the reaction temperature is 350°C and the reaction pressure is 0.1MPa.

[0036] Example 2

[0037] A catalyst for methacrylate synthesis, the raw materials of which include: 3g of tetrabutyl orthosilicate, 10g of soybean lecithin, 2g of cholesterol, 1g of zirconium nitrate, 10g of cesium nitrate and 2g of graphene oxide.

[0038] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0039] S1. Tetrabutyl orthosilicate, soybean lecithin and cholesterol were added to 30 g of chloroform and mixed evenly. The chloroform was removed by rotary evaporation. The mixture was added to 30 g of phosphate buffer solution with a pH of 5.2-6.5. Zirconium nitrate was added and ultrasonically treated for 20 min at an ultrasonic frequency of 6 kHz. The pH value of the system was adjusted to 8.5-9.5 with aqueous ammonia. The mixture was stirred at room temperature for 2 h, filtered, vacuum dried, calcined at 450° C. for 2 h, and cooled to room temperature to obtain a composite carrier.

[0040] S2. Add cesium nitrate and graphene oxide to 30 g of deionized water and stir evenly, add the composite carrier, perform ultrasonic treatment at 50°C for 2 h, the ultrasonic frequency is 6 kHz, let stand for 10 h, put into the inner tank of the hydrothermal reactor, perform hydrothermal reaction at 210°C for 10 h, cool to room temperature, filter, wash, and freeze-dry.

[0041] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:10, and the feed space velocity is 6.5h-1 , the reaction temperature is 400°C and the reaction pressure is 0.2MPa.

[0042] Example 3

[0043] A catalyst for methacrylate synthesis, the raw materials of which include: 1.5 g of tetrabutyl orthosilicate, 9 g of soybean lecithin, 1.3 g of cholesterol, 0.8 g of zirconium nitrate, 7 g of cesium nitrate, and 1.8 g of graphene oxide.

[0044] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0045] S1. Tetrabutyl orthosilicate, soybean lecithin and cholesterol were added to 22g of chloroform and mixed evenly. The chloroform was removed by rotary evaporation, and the mixture was added to 25g of phosphate buffer solution with a pH of 5.2-6.5. Zirconium nitrate was added and ultrasonically treated for 12min at an ultrasonic frequency of 5kHz. The pH value of the system was adjusted to 8.5-9.5 with ammonia water. The mixture was stirred at room temperature for 80min, filtered, vacuum dried, calcined at 445°C for 80min, and cooled to room temperature to obtain a composite carrier.

[0046] S2. Add cesium nitrate and graphene oxide to 28 g of deionized water and stir evenly, add the composite carrier, ultrasonically treat at 42°C for 100 min, the ultrasonic frequency is 3 kHz, let stand for 9 h, put into the inner tank of the hydrothermal reactor, hydrothermally react at 200°C for 9 h, cool to room temperature, filter, wash, and freeze-dry.

[0047] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:6, and the feed space velocity is 6h -1 , the reaction temperature is 360°C and the reaction pressure is 0.17MPa.

[0048] Example 4

[0049] A catalyst for methacrylate synthesis, the raw materials of which include: 2.5 g of tetrabutyl orthosilicate, 7 g of soybean lecithin, 1.7 g of cholesterol, 0.2 g of zirconium nitrate, 9 g of cesium nitrate, and 1.2 g of graphene oxide.

[0050] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0051] S1. Tetrabutyl orthosilicate, soybean lecithin and cholesterol were added to 28g of chloroform and mixed evenly. The chloroform was removed by rotary evaporation. The mixture was added to 15g of phosphate buffer solution with a pH of 5.2-6.5. Zirconium nitrate was added and ultrasonically treated for 18min at an ultrasonic frequency of 3kHz. The pH value of the system was adjusted to 8.5-9.5 with ammonia water. The mixture was stirred at room temperature for 100min, filtered, vacuum dried, calcined at 420°C for 100min, and cooled to room temperature to obtain a composite carrier.

[0052] S2. Add cesium nitrate and graphene oxide to 22 g of deionized water and stir evenly, add the composite carrier, perform ultrasonic treatment at 48°C for 80 min with an ultrasonic frequency of 5 kHz, let stand for 7 h, put into the inner tank of a hydrothermal reactor, perform hydrothermal reaction at 205°C for 7 h, cool to room temperature, filter, wash, and freeze-dry.

[0053] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:8, and the feed space velocity is 4h -1 , the reaction temperature is 390°C and the reaction pressure is 0.13MPa.

[0054] Example 5

[0055] A catalyst for methacrylate synthesis, the raw materials of which include: 2g of tetrabutyl orthosilicate, 8g of soybean lecithin, 1.5g of cholesterol, 0.5g of zirconium nitrate, 8g of cesium nitrate, and 1.5g of graphene oxide.

[0056] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0057] S1. Tetrabutyl orthosilicate, soybean lecithin and cholesterol were added to 25 g of chloroform and mixed evenly. The chloroform was removed by rotary evaporation. The mixture was added to 20 g of phosphate buffer solution with a pH of 5.2-6.5. Zirconium nitrate was added and ultrasonically treated for 15 min at an ultrasonic frequency of 4 kHz. The pH value of the system was adjusted to 8.5-9.5 with aqueous ammonia. The mixture was stirred at room temperature for 90 min, filtered, vacuum dried, calcined at 440° C. for 90 min, and cooled to room temperature to obtain a composite carrier.

[0058] S2. Add cesium nitrate and graphene oxide to 25 g of deionized water and stir evenly, add the composite carrier, perform ultrasonic treatment at 45°C for 90 min, the ultrasonic frequency is 4 kHz, let stand for 8 h, put into the inner tank of the hydrothermal reactor, perform hydrothermal reaction at 205°C for 8 h, cool to room temperature, filter, wash, and freeze-dry.

[0059] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:7, and the feed space velocity is 5h -1 , the reaction temperature is 380°C and the reaction pressure is 0.15MPa.

[0060] Comparative Example 1

[0061] A catalyst for methacrylate synthesis, the raw materials of which include: 2g of tetrabutyl orthosilicate, 8g of soybean lecithin, 1.5g of cholesterol, 0.5g of zirconium nitrate, 8g of cesium nitrate, and 1.5g of graphene oxide.

[0062] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0063] S1. Tetrabutyl orthosilicate, soybean lecithin and cholesterol were added to 25 g of chloroform and mixed evenly. The chloroform was removed by rotary evaporation. The mixture was added to 20 g of phosphate buffer solution with a pH of 5.2-6.5 and ultrasonically treated for 15 min. The ultrasonic frequency was 4 kHz. The pH value of the system was adjusted to 8.5-9.5 with ammonia water. The mixture was stirred at room temperature for 90 min. The mixture was filtered and dried in vacuum. The mixture was calcined at 440° C. for 90 min and cooled to room temperature to obtain a composite carrier.

[0064] S2. Add cesium nitrate, zirconium nitrate and graphene oxide to 25g of deionized water and stir evenly, add the composite carrier, ultrasonically treat at 45°C for 90min and the ultrasonic frequency is 4kHz, let stand for 8h, put into the inner tank of the hydrothermal reactor, hydrothermally react at 205°C for 8h, cool to room temperature, filter, wash and freeze-dry.

[0065] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:7, and the feed space velocity is 5h -1 , the reaction temperature is 380°C and the reaction pressure is 0.15MPa.

[0066] Comparative Example 2

[0067] A catalyst for methacrylate synthesis, the raw materials of which include: 2g of tetrabutyl orthosilicate, 8g of soybean lecithin, 1.5g of cholesterol, 0.5g of zirconium nitrate, 8g of cesium nitrate, and 1.5g of graphene oxide.

[0068] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0069] S1, adding soybean lecithin and cholesterol to 25g of chloroform and mixing evenly, removing chloroform by rotary evaporation, adding to 20g of phosphate buffer solution with pH=5.2-6.5, adding zirconium nitrate and ultrasonic treatment for 15min, the ultrasonic frequency is 4kHz, using ammonia water to adjust the pH value of the system to 8.5-9.5, stirring at room temperature for 90min, filtering, vacuum drying, adding tetrabutyl orthosilicate and mixing evenly, roasting at a temperature of 440°C for 90min, and cooling to room temperature to obtain a composite carrier;

[0070] S2. Add cesium nitrate and graphene oxide to 25 g of deionized water and stir evenly, add the composite carrier, perform ultrasonic treatment at 45°C for 90 min, the ultrasonic frequency is 4 kHz, let stand for 8 h, put into the inner tank of the hydrothermal reactor, perform hydrothermal reaction at 205°C for 8 h, cool to room temperature, filter, wash, and freeze-dry.

[0071] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:7, and the feed space velocity is 5h -1 , the reaction temperature is 380°C and the reaction pressure is 0.15MPa.

[0072] Comparative Example 3

[0073] A catalyst for synthesizing methacrylate, the raw materials of which include: 2g of tetrabutyl orthosilicate, 0.5g of zirconium nitrate, 8g of cesium nitrate and 1.5g of graphene oxide.

[0074] The method for preparing the above-mentioned catalyst for methacrylate synthesis comprises the following steps:

[0075] S1. Add tetrabutyl orthosilicate to 20 g of phosphate buffer solution with a pH of 5.2-6.5, add zirconium nitrate and ultrasonically treat for 15 min, the ultrasonic frequency is 4 kHz, and the pH value of the system is adjusted to 8.5-9.5 with ammonia water. Stir at room temperature for 90 min, filter, vacuum dry, calcine at 440° C. for 90 min, and cool to room temperature to obtain a composite carrier;

[0076] S2. Add cesium nitrate and graphene oxide to 25 g of deionized water and stir evenly, add the composite carrier, perform ultrasonic treatment at 45°C for 90 min, the ultrasonic frequency is 4 kHz, let stand for 8 h, put into the inner tank of the hydrothermal reactor, perform hydrothermal reaction at 205°C for 8 h, cool to room temperature, filter, wash, and freeze-dry.

[0077] The method for using the above-mentioned methacrylate synthesis catalyst is as follows: the above-mentioned catalyst is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:7, and the feed space velocity is 5h -1, the reaction temperature is 380°C and the reaction pressure is 0.15MPa.

[0078] The specific surface area and pore volume of the catalysts obtained in Example 5 and Comparative Examples 1-3 were measured using the BET method. Figure 1 As shown, the specific surface area and pore volume of the catalyst obtained in Example 5 are both the highest, which are better than those of Comparative Examples 1-3 (P < 0.05).

[0079] In Example 5 and Comparative Examples 1-3, methacrylate was synthesized by catalysis, and the products thereof were mainly methacrylate and water, and also included unreacted methyl propionate and some by-products (such as propionic acid (PA), methacrylic acid (MAA)), etc.

[0080] The liquid products obtained after the reaction were quantitatively analyzed by gas chromatography, and the chromatographic conditions were as follows: injection port temperature 150°C, detector temperature 250°C, column box temperature was programmed to rise from 80°C for 5 min, 15°C / min to 190°C for 5 min, and then to 220°C for 1 min. The split ratio was 20:1, and the carrier gas was high-purity nitrogen at a pressure of 0.4 MPa.

[0081] Calculate each indicator according to the following formula:

[0082] Formaldehyde conversion rate (mol%) = amount of reacted formaldehyde / amount of supplied formaldehyde × 100%

[0083] Methyl propionate conversion rate (mol%) = amount of methyl propionate reacted / amount of methyl propionate supplied × 100%

[0084] Methacrylate selectivity (mol%) = amount of methacrylate produced / amount of methyl propionate supplied × 100%

[0085] Methacrylate yield (mo%) = methyl propionate conversion × methacrylate selectivity × 100

[0086] like Figure 2 and Figure 3 As shown, when the catalyst obtained in Example 5 was used for catalytic reaction, the formaldehyde conversion rate, methyl propionate conversion rate, methacrylate selectivity and methacrylate yield were all the highest, which were better than those of Comparative Examples 1-3 (P < 0.05).

[0087] After the above catalytic reaction, each group of catalysts was taken out, calcined at 450°C for regeneration, and then the catalytic reaction was continued. This process was repeated 5 times, and the methacrylate selectivity was used to characterize the cyclic performance of each group of catalysts.

[0088] like Figure 4As shown, after 5 cycles, the catalytic performance of each group of catalysts decreased. This is because during the cyclic catalytic process, products are continuously deposited on the catalyst surface, which reduces the specific surface area and covers the active centers, resulting in partial deactivation of the catalyst. The catalytic performance of the catalyst obtained in Example 5 is always better than that of Comparative Examples 1-3 (P < 0.05).

[0089] The applicant believes that the reason for the above results is that the present invention adopts tetrabutyl orthosilicate and phospholipids, cholesterol compounding, tetrabutyl orthosilicate is confined in the double-layer hydrophobic structure of phospholipid vesicles, zirconium nitrate is loaded outside the double-layer hydrophilic structure of phospholipid vesicles, and in an alkaline environment, tetrabutyl orthosilicate is hydrolyzed in the hydrophobic layer and zirconium nitrate forms a precipitation structure layer loaded outside the closed double-layer structure; After calcination, a special structure of a deposited zirconium layer coated with silicon dioxide is formed, which not only has a large specific surface area, effectively increases the specific surface area of ​​the catalyst, and has high catalytic activity, but also has good loading effect on cesium nitrate and graphene oxide, and has high structural stability. At the same time, the present invention can effectively avoid the aggregation or agglomeration of active cesium and zirconium on the surface of the carrier, ensure high dispersion, and the interaction between the carrier, the active component cesium and zirconium are evenly dispersed on the carrier with a relatively large surface area, not only exposing more active centers, but also having high catalytic activity, and can slow down the deactivation of the catalytic process, effectively extending the catalytic life.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A catalyst for methacrylate synthesis, characterized in that: The raw materials include, by mass, 1-3 parts of tetrabutyl orthosilicate, 5-10 parts of phospholipids, 1-2 parts of cholesterol, 0.1-1 parts of zirconium nitrate, 5-10 parts of cesium nitrate and 1-2 parts of graphene oxide.

2. The catalyst for methacrylate synthesis according to claim 1, characterized in that The phospholipid is egg yolk lecithin or soybean lecithin.

3. The catalyst for methacrylate synthesis according to claim 1, characterized in that The particle size of graphene oxide is 3-10 μm and the bulk density is 0.06-0.07 g / cm 3 .

4. A method for preparing a catalyst for methacrylate synthesis according to any one of claims 1 to 3, characterized in that: The steps include: S1. Add tetrabutyl orthosilicate, phospholipids and cholesterol to chloroform and mix evenly, remove chloroform by rotary evaporation, add to phosphate buffer solution, add zirconium nitrate and ultrasonically treat for 10-20 minutes, adjust the pH value of the system to 8.5-9.5, stir at room temperature for 1-2 hours, filter, vacuum dry, roast at 400-450° C. for 1-2 hours, and cool to room temperature to obtain a composite carrier; S2. Add cesium nitrate and graphene oxide to deionized water and stir evenly, add the composite carrier, ultrasonically treat at 40-50°C for 1-2h, let stand for 5-10h, hydrothermally react at 195-210°C for 5-10h, cool to room temperature, filter, wash, and freeze-dry.

5. The method for preparing the catalyst for methacrylate synthesis according to claim 4, characterized in that: In S1, the pH value of the phosphate buffer solution is 5.2-6.

5.

6. The method for preparing the catalyst for methacrylate synthesis according to claim 4, characterized in that: In S1, the ultrasound frequency is 2-6kHz.

7. The method for preparing the catalyst for methacrylate synthesis according to claim 4, characterized in that: In S2, the ultrasound frequency is 2-6kHz.

8. A method for using the catalyst for methacrylate synthesis according to any one of claims 1 to 3, characterized in that: The catalyst for methacrylate synthesis according to any one of claims 1 to 3 is filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate is 1:5-10, and the feed space velocity is 3.5-6.5h -1 , the reaction temperature is 350-400℃.

9. The method for using the methacrylate synthesis catalyst according to claim 8, characterized in that: The reaction pressure is 0.1-0.2MPa.